Endoscopic ultrasound-guided fine-needle aspiration of pelvic lesions via the upper and lower gastrointestinal tract approaches - Mita, Naoki (BMC Gastroenterol, 2021)
BACKGROUND: Combining upper and lower gastrointestinal tract (GI) approaches allows expansion of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) indications for pelvic lesions. The upper GI approach has been used for pelvic lesions around the level of the aortoiliac bifurcation in our institution. The aim of this study is to evaluate the feasibility and safety of EUS-FNA for pelvic lesions via the upper and lower GI approaches. METHODS: All consecutive patients who underwent EUS-FNA for the pelvic lesion between January 2008 and December 2018 were retrospectively analyzed. Pelvic lesions were defined as lesions located around and below the aortoiliac bifurcation level. The primary outcome was technical success rate, and the secondary outcomes were the diagnostic capability of EUS-FNA for malignancy and the safety. RESULTS: EUS-FNA for pelvic lesions was performed in 49 patients: upper and lower GI approaches were used in 28 and 21 patients, respectively. The technical success rates were 91.8% (45/49) in all patients: 89.3% (25/28) and 95.2% (20/21) with the upper and lower GI approaches, respectively. Among patients who achieved technical success, the diagnostic accuracy for malignancy was 97.8% (44/45) in all patients: 100% (25/25) and 95.0% (19/20) with the upper and lower GI approaches, respectively. One (2.0%) patient developed an adverse event of sigmoid colon perforation. CONCLUSIONS: EUS-FNA for pelvic lesions via the upper and lower GI approaches was a safe, feasible, and effective method, although careful endoscopic manipulation is required to avoid perforation, especially with the lower GI approach. Further large-scale, well-designed studies are needed to validate our findings.